A Comparison between Fuzzy-PSO Controller and PID-PSO Controller for Controlling a DC Motor - Ali Ghareaghaji (Institute of Advanced Engineering and Science, 2015)
The Direct current motors are in different types and there are several methods for controlling of their speed. In this paper two ways for speed controlling suggested. First a fuzzy logic speed controller for DC motor is designed and it’s parameter calculated by Particle Sward Optimization (PSO). The speed controller designed according to fuzzy rules, then for having better performance, the controller optimized with PSO. Secondly a PID controller that it’s parameter find by PSO, is used for speed controlling of a DC motor. At the end the performance of fuzzy logic controller compared with PID controller. The results show that fuzzy-PSO controller has better performance.